Biomechanical analysis of upper limb during the use of touch screen: motion strategies identification. Issue 3 (4th March 2017) - Jacquier-Bret, Julien; Gorce, Philippe; Motti Lilian, Genaro; Vigouroux, Nadine
Abstract: Nowadays touch technology is growing and developers try to make it ever more intuitive and easier to use. This present work focused on the upper limb joint coordination during the achievement of puzzles on touch screen. A 5-inch and 10-inch devices were used to perform 9 and 16 pieces puzzles dragged with digits. The conclusions showed an increase in joint solicitation with the number of piece and the touch screen size. Moreover, three interactions strategies proved to be an evidence: the 'wrist strategy' preferentially implying wrist flexion/extension, the 'elbow strategy' preferentially implying the elbow flexion/extension and the 'neutral strategy' mobilising equally the two joints. From an ergonomic point of view, the data about how the upper limb segments are mobilised while interacting with the screen could be relevant to increase the adaptability of the devices to the user, including users with motor impairments. Practitioner Summary: Information about the biomechanical organisation of movement during interaction with touch devices appears relevant in order to develop applications adapted to the motor capacities of users. From the analysis of joint angles when performing several times a puzzle with healthy subjects, three motor strategies were highlighted.